2020
DOI: 10.2147/cmar.s228629
|View full text |Cite
|
Sign up to set email alerts
|

<p>Knockdown of ATAD2 Inhibits Proliferation and Tumorigenicity Through the Rb-E2F1 Pathway and Serves as a Novel Prognostic Indicator in Gastric Cancer</p>

Abstract: The aim of the present study was to examine the expression of ATAD2 in gastric cancer (GC) specimens and to evaluate its correlation with clinicopathologic features, including survival of GC patients. The potential roles of ATAD2 in the GC cell proliferation, apoptosis, and tumour growth were further explored. Materials and Methods: Quantitative reverse transcription-polymerase chain reaction (qRT-PCR), Western blotting and immunohistochemistry (IHC) were applied to determine the mRNA and protein expression of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 24 publications
0
11
0
Order By: Relevance
“…The pRB‐E2F pathway tightly regulates ATAD2 expression, which is essential for the growth of normal and cancer cells. As a direct binding partner for both E2F and c‐Myc, ATAD2 induces the expression of genes that facilitate cell cycle progression and inhibition of apoptosis in many different types of cancers, including breast, lung and prostate tumors 48 . Also, Wu et al 49 proposed that ATAD2 might cooperate with the c‐Myc to control the level of SMO and GLI1 , leading to the Hedgehog (Hh) pathway and feedback of the Hh pathway activation in liver tumor cells.…”
Section: Discussionmentioning
confidence: 99%
“…The pRB‐E2F pathway tightly regulates ATAD2 expression, which is essential for the growth of normal and cancer cells. As a direct binding partner for both E2F and c‐Myc, ATAD2 induces the expression of genes that facilitate cell cycle progression and inhibition of apoptosis in many different types of cancers, including breast, lung and prostate tumors 48 . Also, Wu et al 49 proposed that ATAD2 might cooperate with the c‐Myc to control the level of SMO and GLI1 , leading to the Hedgehog (Hh) pathway and feedback of the Hh pathway activation in liver tumor cells.…”
Section: Discussionmentioning
confidence: 99%
“…The pRb is a CDK4/CDK6 target, and as soon as cyclin D1 combines with CDK4/CDK6, pRb is phosphorylated and ppRb is liberated from E2F. ATAD2 binds to the transcription factors E2F and c-MYC to promote proliferation-related and anti-apoptotic gene expression, causing the occurrence and development of GC [ 21 , 22 ]. Furthermore, ATAD2 may interact with estrogen receptor 1 (ESR1) to regulate nuclear receptor coactivator 1 (NCOA1) and protein arginine methyltransferase 1 (PRMT1) to cause epigenetic changes in GC ( Figure 2 ) [ 23 ].…”
Section: The Role Of Atad2 In Human Malignant Tumorsmentioning
confidence: 99%
“…It has been found that ATAD2 can be used as one of the candidate genes for paclitaxel resistance and become a potential new marker for predicting paclitaxel resistance in patients with peritoneal metastasis of GC [ 106 ]. ATAD2 overexpression is correlated with the clinical stage, depth of tumor invasion, lymph node, and distant metastasis of GC and is an independent factor in the prognosis of GC patients [ 21 , 107 ].…”
Section: The Role Of Atad2 In Human Malignant Tumorsmentioning
confidence: 99%
“…Moreover, SPIN1 could form a positive feedback loop with E2F1 to promote the development of GC ( 128 ). Furthermore, ATAD2 knockdown in GC cells led to reduced levels of cyclin D1, cyclin E, E2F1 and RB phosphorylation, thus inhibiting proliferation and cell cycle progression ( 129 ). Interestingly, decrease of intracellular chloride ion concentration could increase the level of p21 and reduce the phosphorylation of CDK2 and RB ( 130 ).…”
Section: Upstream Regulators Of the Rb-e2f Pathway In Gastric Cancermentioning
confidence: 99%